Pemanfaatan Kecerdasan Buatan (AI) dalam Pembelajaran bagi Mahasiswa - Amsal, Mutiara Felicita; Darma Sagita, Dony (Fakultas Ilmu Pendidikan Universitas Negeri Padang, 2024)
The focus of education in the 4.0 era is not only on academic knowledge, but also on the development of important skills such as critical thinking, problem solving, creativity, collaboration, and digital literacy. These are skills needed to adapt to the changing world of work. The use of technologies such as the Internet of Things (IoT), big data, artificial intelligence (AI), and augmented reality (AR) has changed the way teachers and students interact. Learning can be done online with digital platforms, allowing access to wider information and flexibility of time. Artificial intelligence (AI) has changed many aspects of life, including education. This article aims to explore the use of AI in learning for students, with a focus on effectiveness, impact, and challenges faced. Through a literature review and case studies, this research identifies how AI can improve the learning experience, personalize education, and increase student engagement.